Effect of white blood cells on sperm parameters and semen for Asthenozoo spermic infertile patients . - Ù…ØØ³Ù† ÙƒØ§Ø¸Ù… ØØ³Ù† Ø£Ù„Ù…Ø±Ø´Ø¯ÙŠ; ØµØ§ØØ¨ ÙŠØÙŠÙ‰ ØØ³Ù† Ø§Ù„Ù…Ø±Ø´Ø¯ÙŠ (Al-Qadisiyah Journal of Pure Science, 2017)
This study was performed on (80) patient complaining from Asthenozoospermia. This study was conducted to evaluate the effect and relationship between white blood cells and each of sperm and semen parameters .The result of this study was revealed a significant decrease (p<0.01) in semen volume sperm concentration, sperm motility percent and sperm grade activity while the result showed significant increase( p<0.01 ) of liqufaction time . The results were revealed no significant effect of normal sperm morphology percent . In conclusion , the leukocyte effect in sperm and semen parameters that related with men ability for fertilization and pregnancy rates .